Maternal perinatal depression and child neurocognitive development: A relationship still to be clarified - Severo, Melania; Ventriglio, Antonio; Bellomo, Antonello; Iuso, Salvatore; Petito, Annamaria (Frontiers in Psychiatry, 2023)
Pregnancy frequently is associated with emotional conditions such as anxiety and depression. Perinatal depression has an incidence of around 12%. Only recently researcher put the attention on the effects of pre- and postpartum psychopathology on infant neurocognitive development. Neurobiology studies indicate that perinatal maternal depression can significantly affect the structure and function of children's prefrontal cortex and modulate the development of cognitive abilities from intrauterine life. On the topic, the scientific literature appears ambiguous, reporting mixed results. Some studies have found no significant differences in developmental outcomes between prenatal and postpartum exposure to maternal depression, others have suggested a greater burden of depression in pregnancy than in postpartum, and still others have emphasized the role of chronicity of symptoms rather than the period of onset. Few studies have examined the effects of different developmental trajectories of maternal depression on children's neurocognitive outcomes. The assessment of maternal health has for years been limited to postpartum depression often neglecting the timing of onset, the intensity of symptoms and their chronicity. These aspects have received less attention than they deserve, especially in relation to the effects on children's neurocognitive development. The aim of this Perspective was to highlight inconsistencies and gaps that need to be filled in the approach to the study of this problem. Given the wide heterogeneity of data in the current literature, further studies are needed to clarify these interactions. This Perspective provides an overview of current progress, future directions, and a presentation of the authors' views on the topic.